PENGARUH PENGHARGAAN, HUKUMAN DAN KOMPENSASI TERHADAP MOTIVASI KERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH KABUPATEN MAJENE - Fajar Rakasiwi Syamsuddin; Nurdiyah Nurdiyah; Saddam Husain Thamrin (Jurnal Ilmiah Hospitality, 2022)
The problem of this study is whether Reward, Punishment and Compensation affect the work motivation of employees at the Majene Regency Regional Personnel Agency. This study aims to measure the effect of Reward, Punishment and Compensation on employee work motivation using quantitative data if the data is in the form of numbers, or quantitative data that is evaluated (scoring). Data in the form of numbers or scores obtained using data collection tools, and the answers in the form of a series of scores or questions that are equated Based on the data that has been collected and hypothesis testing with multiple regression analysis has been carried out, the conclusion of this study is that Reward, Punishment and Compensation have a positive and significant effect on employee work motivation. The higher the award, the more the employee's work motivation will increase